(untitled) (Khairulummah, 2023)
While Afghanistan has made progress towards democratic governance, there are still challenges to be addressed in terms of creating a fair and inclusive political system that represents all Afghans. Among these challenges, one is the development of political parties in Afghanistan. The article provides an overview of the history of political parties in Afghanistan, from 1940 to 2010. It highlights the suppression faced by political movements and political parties under various regimes, and the failure to establish a modern democratic state in Afghanistan. This article attempts to explore the reasons of the suppression of political parties in Afghanistan. It also outlines the legal recognition and restrictions placed on political parties under the constitution of 2004 and the Political Parties law of 2003, as well as the flawed electoral laws adopted in 2004.